2016
DOI: 10.1007/s00467-016-3571-6
|View full text |Cite|
|
Sign up to set email alerts
|

Hypomagnesemia and increased risk of new-onset diabetes mellitus after transplantation in pediatric renal transplant recipients

Abstract: BackgroundNew-onset diabetes after transplantation (NODAT) is a significant co-morbidity following kidney transplantation. Lower post-transplant serum magnesium levels have been found to be an independent risk factor for NODAT in adult kidney transplant recipients.MethodsWe undertook a retrospective analysis of risk factors for NODAT in pediatric renal transplant recipients at our institution with the aim of determining if hypomagnesemia confers a significant risk of developing NODAT in this patient population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…In this study, we found that children treated with CNI showed significantly lower serum magnesium levels and that they were significantly more likely to develop hypomagnesemia. This is in line with previous findings in children [ 31 , 32 , 33 , 34 ] and adults [ 21 ]. In adults and animal models, it was shown that hypomagnesemia is caused by renal magnesium wasting [ 20 , 21 , 35 ].…”
Section: Discussionsupporting
confidence: 94%
“…In this study, we found that children treated with CNI showed significantly lower serum magnesium levels and that they were significantly more likely to develop hypomagnesemia. This is in line with previous findings in children [ 31 , 32 , 33 , 34 ] and adults [ 21 ]. In adults and animal models, it was shown that hypomagnesemia is caused by renal magnesium wasting [ 20 , 21 , 35 ].…”
Section: Discussionsupporting
confidence: 94%
“…Hypomagnesemia and high tacrolimus levels were significant and independent risk factors for PTDM ( p = 0.01 and p < 0.001, respectively). No association between hypomagnesemia and tacrolimus levels was observed, suggesting that both risk factors were independent from each other [ 55 ]. Conversely, in a cohort study of 451 pediatric solid organ transplant recipients, Chanchlani et al failed to identify an association between hypomagnesemia and PTDM.…”
Section: Serum Magnesium and New-onset Diabetes Mellitus After Tramentioning
confidence: 99%
“…A retrospective analysis performed by Hayes and colleagues found low serum magnesium to be an independent risk factor for new‐onset diabetes among pediatric renal transplant recipients. An additional finding of this study showed that high tacrolimus trough concentrations conferred additional risk for development of new‐onset diabetes . Most concerning are reports of decreased allograft survival in renal transplant patients who have hypomagnesemia .…”
Section: Introductionmentioning
confidence: 63%